The Effect of Net Income, Company’s value, Sales growth and Institutional Ownership on The Dividend Policy of Syariah Stocks and Common stocks listed in BEI in 2013-2015 - Maya Matofani; Taufiq Taufiq; Rela Sari (Penerbit Jurnal Indonesia, 2021)
This empirical study aims to examine The effect of Net Income, Company’s value, Sales growth and Institutional Ownership on The Dividend Policy of Syariah Stocks and Common stocks listed in BEI in 2013-2015. The sampling method used is purposive sampling amounted to 50 samples that consist of 30 syariah stocks and 20 common stocks. Multiple regression analysis and chow test are used as data analysis method. The results of F test shows that simultaneously, net income, company’s value, sales growth and institutional ownership affect the dividend policy on both syariah and common stocks. However, when tested partially, on syariah stocks, only net income and sales growth that have positive effect on the dividen policy while on common stocks, only net income and company’s value have positive effect on the policy. From the chow test result, it shows that there is a difference between the effect of net income, company’s value, sales growth and institutional ownership on the dividen policy of syariah stocks and common stocks..